Interatrial block and interatrial septal thickness in patients with paroxysmal atrial fibrillation undergoing catheter ablation: Long‐term follow‐up study. Issue 4 (25th December 2016) - Gul, Enes E.; Pal, Raveen; Caldwell, Jane; Boles, Usama; Hopman, Wilma; Glover, Benedict; Michael, Kevin A.; Redfearn, Damian; Simpson, Chris; Abdollah, Hoshiar; Baranchuk, Adrian
Abstract : Background: Interatrial block (IAB) is a strong predictor of recurrence of atrial fibrillation (AF). IAB is a conduction delay through the Bachman region, which is located in the upper region of the interatrial space. During IAB, the impulse travels from the right atrium to the interatrial septum (IAS) and coronary sinus to finally reach the left atrium in a caudocranial direction. No relation between the presence of IAB and IAS thickness has been established yet. Objective: To determine whether a correlation exists between the degree of IAB and the thickness of the IAS and to determine whether IAS thickness predicts AF recurrence. Methods: Sixty‐two patients with diagnosis of paroxysmal AF undergoing catheter ablation were enrolled. IAB was defined as P‐wave duration ≥120 ms. IAS thickness was measured by cardiac computed tomography. Results: Among 62 patients with paroxysmal AF, 45 patients (72%) were diagnosed with IAB. Advanced IAB was diagnosed in 24 patients (39%). Forty‐seven patients were male. During a mean follow‐up period of 49.8 ± 22 months (range 12–60 months), 32 patients (51%) developed AF recurrence. IAS thickness was similar in patients with and without IAB (4.5 ± 2.0 mm vs. 4.0 ± 1.4 mm; p = .45) and did not predict AF. Left atrial size was significantly enlarged in patients with IAB (40.9 ± 5.7 mm vs. 37.2 ± 4.0 mm; p = .03). Advanced IAB predicted AF recurrence after the ablation (OR: 3.34, CI: 1.12–9.93; p = .03). Conclusions: IAS thickness was not significantly correlated to IAB and did not predict AF recurrence. IAB as previously demonstrated was an independent predictor of AF recurrence.